Quantitative and Morphometric Study of Adipose Tissue from Abdomen in Adult Women of Hyderabad (Medical Forum Monthly, 2024)
Objective: To determine adipocytes count per unit area in the superficial subcutaneous layer of the abdomen of an adult woman.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at Department of Anatomy, Isra University Hospital Hyderabad from July 2011 to December 2011.Materials and method: 80 adult women including 40 obese and 40 non obese for different abdominal surgeries visited in the Isra university hospital Hyderabad. Superficial subcutaneous layer of the abdominal adipose tissue were obtained during surgery. Tissues were processed for routine H&E staining. After processing, the number of adipocytes was counted through ocular grid microscopy method.Results: In obese, the mean number of adipocytes was 119.02+5.81 with range of 100-140 and in non-obese, the mean number of adipocytes was 79.02+6.02 with range of 50-98.The result showed a significant (p<0.05) increase number of adipocytes in obese women as compare to non obese women.Conclusion: From this study it was conclude that in obese women there is increased number of adipocytes as compare to non obese women. As increased number of adipocytes enhance the cardiovascular as well as metabolic diseases and producing fatal health risks. Therefore there is need to elaborate the cause of disorder and its proper diagnosis through counting or assessment of adipocytes which helpful for management of diseases